Diagnosing the Mutations and the Effect Concentration Chromium Cr (VI) in KRAS gene in Exon1 for lung Cancer Patients in Najaf Governorate - Farah Khalid H. AL-Mayali 1, Mohammad Jaber M. AL-Zeyadi 2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The importance of the current study lies in investigating the mutations in the exon1 of the KRAS gene asoncogenes, the presence of mutations associated with lung cancer and the lack of response to chemotherapy.As well as to know the relationship between diagnosed mutations and concentration of chromium . Thesestudy was conducted at AL-Furat AL-Awsat oncology Center In Najaf for period from December / 2019 toApril / 2020 , on the study included 60 patients who were diagnosed with lung cancer and 22 healthy peoplewhere used as control group . the diagnosis of mutation in both patients and healthy subjects has been studiedand compared. Then revealing the relationship between mutations and health status to see the effect ofmutations on them. The present results showed that there were many mutations found in KRAS gene exon1,42 genetic mutations in the KRAS gene were detected in exon1 , and these mutations appeared in varyingproportions in both patients people, as is evident in In exon1, the frequency of mutation were rs104894361SNP were in 11(18.33%) , rs121913236 SNP 13 (21.7%) and rs104894366 were 18 (30%) , distribution in 24patients . more frequency mutations appeared in four patients ( 2,17,27,42 ) (6.7%) where found three typesof mutations (rs104894361 SNP , 21913236 SNP and rs104894366 ) those patients have highest recurrenceof (1.330, 1.153, 1.224 -1.490) Respectively. While 10 patients (16.7 %) (21,46,9,34,35,30,12,37,14, 39)have only two mutations with distribution in three types also , and 10 patients(16.7 %) were have justone mutation. We found correlation between high Chromium (Cr) concentration in serum of patients withlung cancer compared to healthy. The results of the study showed that there were significant differences(P=0.0001) between the presence of mutations and concentration of chromium, which indicates a relationshipbetween the of mutations and concentration of chromium in the serum the of patient of lung cancer. DNAwas extracted from the blood samples by several DNA extracts and mutations were detected by sequencinganalyzing after amplification by PCR technology